Housing First for older homeless adults with mental illness: a subgroup analysis of the At Home/Chez Soi randomized controlled trial. (16th February 2017) - Chung, Timothy E.; Gozdzik, Agnes; Palma Lazgare, Luis I.; To, Matthew J.; Aubry, Tim; Frankish, James; Hwang, Stephen W.; Stergiopoulos, Vicky
Abstract : Objective: This study compares the effect of Housing First on older (≥50 years old) and younger (18–49 years old) homeless adults with mental illness participating in At Home/Chez Soi, a 24‐month multisite randomized controlled trial of Housing First. Method: At Home/Chez Soi, participants ( n  = 2148) were randomized to receive rent supplements with intensive case management or assertive community treatment, based on their need level for mental health services, or usual care in their respective communities. A subgroup analysis compared older ( n  = 470) and younger ( n  = 1678) homeless participants across baseline characteristics and 24‐month outcomes including housing stability (primary outcome), generic and condition‐specific quality of life, community functioning, physical and mental health status, mental health symptom severity, psychological community integration, recovery, and substance use (secondary outcomes). Results: At 24 months, Housing First significantly improved the percentage of days stably housed among older (+43.9%, 95% confidence interval [CI]: 38.4% to 49.5%) and younger homeless adults (+39.7%, 95% CI: 36.8% to 42.6%), compared with usual care, with no significant differences between age groups (difference of differences = +4.2%, 95% CI: −2.1% to 10.5%, p  = 0.188). Improvements from baseline to 24 months in mental health and condition‐specific quality of life were significantly greater among older homeless adults than among younger homeless adults. Conclusion: Housing First significantly improved housing stability among older and younger homeless adults with mental illness, resulting in superior mental health and quality of life outcomes in older homeless adults compared with younger homeless adults at 24 months. Copyright © 2017 John Wiley & Sons, Ltd.